Strengthening maternal healthcare in Ghana: utilizing the community-based health planning and services model as a vehicle - Baatiema, Linus (Frontiers in Global Women's Health, 2025)
Introduction/aimThis review explores the Community-Based Health Planning and Services (CHPS) model and its impact on maternal healthcare delivery in Ghana's primary healthcare system. It highlights both the achievements and challenges of the initiative, focusing on community involvement, trained human resources, and effective referral linkages.AimTo critically examine how CHPS model contributes to strengthening maternal healthcare delivery in Ghana, by assessing its successes, challenges, and potential for promoting equitable and sustainable health outcome.MethodsThe study systematically reviewed literature from databases including PubMed, Google Scholar, and JSTOR, using keywords related to CHPS, maternal and child healthcare, reproductive health, and community health initiatives. Peer-reviewed articles, reports, and grey literature published within the past 10 years were prioritized, with additional insights drawn from references in the selected studies. The thematic areas were organized into maternal and child health services, reproductive health challenges, community health programs, and CHPS's role in addressing healthcare inequalities.ResultsFindings reveal that, CHPS as a strategy has significant potential to improve maternal health outcomes, reduce mortality rates, and ensure equitable access to care for women in rural and underserved areas. Key challenges such as inadequate funding, staff shortages, political interference, and cultural barriers persist, limiting the model's overall impact.ConclusionThe study provides policy recommendations to enhance the effectiveness of the CHPS model and calls for a collective effort from health sector stakeholders to build a sustainable maternal healthcare system in Ghana.